Barriers (and catalysts) of institutional change: The (almost) non-reform of the Portuguese electoral system (1983–2021) - Carvalho, R.; Freire, A. (Zeitschrift für Vergleichende Politikwissenschaft, 2022)
The literature on electoral system change has focused on the motivations of the political actors who initiate these legislative processes. However, less is known about how contextual factors impact electoral reform approval. The Portuguese case is especially interesting for investigating this question. In the 38-year period studied in this article, only one reduction in the number of MPs and two amendments to the rules governing changes in the electoral system occurred, despite the 11 episodes in which political parties attempted to reform the electoral system. Using a strategy that prioritizes the contextualized analysis of a long period, the goal is to explore the mechanisms—barriers and catalysts—that underlie reform and non-reform. We conclude that the maintenance of the status quo is the result of the combined effectiveness of the barriers—high constitutional and legal barriers, as well as inter and intra-party veto players—and the ineffectiveness of the catalysts—the electoral system ensured political and electoral stability, while simultaneously lowering the risks faced by the main political parties—during the analysed period. We also conclude that the extreme results obtained in the intra-party dimension of the electoral system, which has been the driving force behind the country’s debate on electoral reform, are the only exception to this trend.